KEWENANGAN LEMBAGA PENGELOLA INVESTASI DALAM PENGELOLAAN BARANG MILIK NEGARA DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 1 TAHUN 2004 TENTANG PERBENDAHARAAN NEGARA - Jeffry Leonard P. Tobing; Joko Trio Suroso (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2021)
ABSTRACT Government Regulation Number 74 of 2020 concerning Investment Management Institutions (LPI) confirms that the government grants at least 3 (three) privileges to LPI referring to: 1) Article 72 states that LPI cannot be bankrupted, unless it can be proven in an insolvency condition, 2) Article 55 stipulates that State-Owned Enterprises (BUMN) assets that are used as investment by the central government can be transferred directly to the LPI joint venture, and 3) Article 52 provides special treatment in the event that the annual report consisting of activity reports and financial statements is audited by a public accounting firm selected by the Board of Directors. LPI is based on the approval of the LPI Supervisory Board. The purpose of this research to identify, analyze and provide an overview the limitation of the authority of Investment Management Institutions to avoid conflicts between Government Institutions. This research is included in legal research which is descriptive-qualitative analysis, which describes the applicable laws and regulations related to legal theories and positive law implementation practices concerning problems. This research is included in normative juridical research, which is research that examines and analyzes legal norms that have been set by the competent authorities. The results of the analysis and discussion can be concluded that the authority of the Investment Management Agency (LPI) associated with Law Number 1 of 2014 concerning the State Treasury is carried out by considering the existence of other similar institutions prior to the establishment of the LPI, the role of State-Owned Enterprises (BUMN), as well as the use of goods. State-owned (BMN) as the main capital in attracting investors to invest in Indonesia. Limiting the authority of Investment Management Institutions (LPI) is carried out to avoid conflicts between Government Institutions by limiting the authority to implement regulations under the Ministry of Finance which is directly responsible to the President, and the mechanism for financial supervision in the use of State Property (BMN) by Public Accountants under the legalization of the Supreme Audit Agency (BPK), however, the role of BPK is still needed in the monitoring function and involvement of international public accountants so that aspects of governance and transparency can be demonstrated properly. Keywords: State Property, Authority, and Investment Management Institution